The effects of Src tyrosine kinase inhibitor, saracatinib, on the markers of epileptogenesis in a mixed-sex cohort of adult rats in the kainic acid model of epilepsy - Rao, Nikhil S.; Putra, Marson; Meyer, Christina; Almanza, Aida; Thippeswamy, Thimmasettappa (Frontiers in Molecular Neuroscience, 2023)
Neurodegeneration and neuroinflammation are key processes of epileptogenesis in temporal lobe epilepsy (TLE). A considerable number (∼30%) of patients with epilepsy are resistant to currently available antiseizure drugs and thus there is a need to develop adjunct therapies to modify disease progression. A vast majority of interventional strategies to treat TLE have utilized males which limits the translational nature of the studies. In this study, we investigated the effects of repeated low-dose kainic acid (KA) injection on the initial status epilepticus (SE) and the effects of Src kinase inhibitor, saracatinib (SAR/AZD0530; 20 mg/kg, oral, daily for 7 days), in a mixed-sex cohort of adult Sprague Dawley rats during early epileptogenesis. There were no sex differences in response to KA-induced SE, and neither did the stage of estrus influence SE severity. KA-induced SE caused significant astrogliosis and microgliosis across the hippocampus, piriform cortex, and amygdala. SAR treatment resulted in a significant reduction of microgliosis across brain regions. Microglial morphometrics such as branch length and the endpoints strongly correlated with CD68 expression in the vehicle-treated group but not in the SAR-treated group, indicating mitigation by SAR. KA-induced SE caused significant neuronal loss, including parvalbumin-positive inhibitory neurons, in both vehicle (VEH) and SAR-treated groups. SAR treatment significantly mitigated FJB-positive neuronal counts as compared to the VEH group. There was an increase in C3-positive reactive astrocytes in the VEH-treated group, and SAR treatment significantly reduced the increase in the piriform cortex. C3-positive astrogliosis significantly correlated with CD68 expression in the amygdala (AMY) of VEH-treated rats, and SAR treatment mitigated this relationship. There was a significant increase of pSrc(Y419)-positive microglia in both KA-treated groups with a statistically insignificant reduction by SAR. KA-induced SE caused the development of classical glial scars in the piriform cortex (PIR) in both KA-treated groups, while SAR treatment led to a 42.17% reduction in the size of glial scars. We did not observe sex differences in any of the parameters in this study. SAR, at the dose tested in the rat kainate model for a week in this study mitigated some of the markers of epileptogenesis in both sexes.